Poza normą. Queerowe elementy wczesnej prozy Romana Dmowskiego - Barłowski, Dezydery (Zagadnienia Rodzajów Literackich, 2024)
In this article I focus on the analysis of Roman Dmowski’s early literary work. In this text, my main goal is to show queer themes in the story entitled The Journey to the Ideals. An Eastern Fairy Tale (Wędrówka do ideałów. Bajka Wschodnia) published in 1894. In the first part of the article, I present the characteristics of Roman Dmowski’s literary work. In the second part, I conduct a detailed analysis of the The Journey to the Ideals, paying particular attention to queer elements. In the last part, I present possible interpretations of The Journey to the Ideals. Important aspects of the analysis are the issues of homoeroticism, homophobia and orientalism. In my analysis I use some elements of the theories of Eve Kosofsky Sedgwick and Edward W. Said. The interpretation highlights biographical threads — references to Roman Dmowski’s early socio-political activity, as well as to the social relationships of the author of Myśli nowoczesnego Polaka (primarily the relationship between the young Roman Dmowski and Stefan Żeromski). In the article, I also present the ideological message of The Journey to the Ideals. An Eastern Fairy Tale — the transition from social egalitarianism (left-wing, democratic and inclusive) to Nietzschean philosophy (right-wing, hierarchical and machismo).